An analytical system enabling consistent and long-term measurement of atmospheric dimethyl sulfide. (June 2016) - Jang, Sehyun; Park, Ki-Tae; Lee, Kitack; Suh, Young-Sang
Abstract: We describe here an analytical system capable of continuous measurement of atmospheric dimethylsulfide (DMS) at pptv levels. The system uses customized devices for detector calibration and for DMS trapping and desorption that are controlled using a data acquisition system (based on Visual Basic 6.0/C 6.0) designed to maximize the efficiency of DMS analysis in a highly sensitive pulsed flame photometric detector housed in a gas chromatograph. The fully integrated system, which can sample approximately 6 L of air during a 1-hr sampling, was used to measure the atmospheric DMS mixing ratio over the Atlantic sector of the Arctic Ocean over 3 full annual growth cycles of phytoplankton in 2010, 2014, and 2015, with minimal routine maintenance and interruptions. During the field campaigns, the measured atmospheric DMS mixing ratio varied over a considerable range, from <1.5 pptv to maximum levels of 298 pptv in 2010, 82 pptv in 2014, and 429 pptv in 2015. The operational period covering the 3 full annual growth cycles of phytoplankton showed that the system is suitable for uninterrupted measurement of atmospheric DMS mixing ratios in extreme environments. Moreover, the findings obtained using the system showed it to be useful in identifying ocean DMS source regions and changes in source strength. Highlights: A fully integrated, automated system for the continuous measurement of airborne DMS. The proposed system was proved to be stable for 3 full growth cycles of phytoplankton. The system enabled the measurements of short-term and long-term airborne DMS trends.